Standardisation and quality evaluation of betel leaf based yoghurt - Vidya TA, Seeja Thomachan , Sharon C L , Aneena ER , Surendra Gopal , Berin Pathrose , Lakshmy PS , Suman KT (Indian Journal of Dairy Science, 2024)
Yoghurts are those milk products which are fermented and have a good impact on the human health. Incorporation of herbs or medicinal plants into the yoghurt, can improve the variety as well as the nutritional and therapeutic benefit of the yoghurt. The present study aimed at developing yoghurt incorporated with betel leaf extract and was successful. The incorporation of 15% betel leaf extract had better organoleptic qualities when compared to the other treatments. The nutritional qualities, physicochemical qualities and the shelf life qualities of the betel leaf yoghurt were also studied. The study revealed that the yoghurt had better nutritional qualities and can be stored for atleast 15 days in refrigerated conditions. Further studies have to be carried out to understand the medicinal properties of the prepared yoghurt.